Digital system design with VHDL. - Zwolinski, Mark, ....- (Harlow : Prentice Hall, 2004)
Preface Introduction. Combinational Logic Design. Combinational Logic using VHDL Gate Models. Combinational Building Blocks. Synchronous Sequential Design. VHDL Models of Sequential Logic Blocks. Complex Sequential Systems. Simulating VHDL. VHDL Synthesis. Testing Digital Systems. Design for Testability. Asynchronous Sequential Design. Interfacing with the Analogue World. Appendix A VHDL Standards.Appendix B Verilog Appendix C Shared Variable packages Bibliography Answers to selected exercises
Keywords: VHDL (vhsic hardware description language).